2009
DOI: 10.1017/s0950268809991099
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported complications associated with Campylobacter jejuni infection

Abstract: This study aimed to investigate the occurrence of complications, especially musculoskeletal symptoms, after sporadic Campylobacter jejuni enteritis of domestic origin in Finland. This multi-centre cross-sectional study was conducted during a seasonal peak in 2002. Questionnaires were sent to Campylobacter-positive patients, representing different geographical areas, 2 months after collection of positive stool samples. Medical records were viewed in several cases. Besides antimicrobial susceptibility testing C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…In a questionnaire study of patients with Campylobacter jejuni enteritis, musculoskeletal symptoms were common (39%) but mostly mild, and only 13% visited a physician. The occurrence of ReA in that study was 4% (9).…”
Section: Discussionmentioning
confidence: 56%
“…In a questionnaire study of patients with Campylobacter jejuni enteritis, musculoskeletal symptoms were common (39%) but mostly mild, and only 13% visited a physician. The occurrence of ReA in that study was 4% (9).…”
Section: Discussionmentioning
confidence: 56%
“…Thirty-seven studies reported ReA following Campylobacter ( n  = 19) and NTS infections ( n  = 26) (Buxton et al, 2002, Bremell et al, 1991, Dworkin et al, 2001, Eastmond, 1983, Ekman et al, 2000, Gumpel et al, 1981, Hakansson et al, 1976, Hannu et al, 2002a, Hannu et al, 2002b, Helms et al, 2006, Pitkanen et al, 1981, Lee et al, 2005, Locht et al, 1993, Locht and Krogfelt, 2002, Locht et al, 2002, Mattila et al, 1994, Mattila et al, 1998, McColl et al, 2000, Petersen et al, 1996, Pitkanen et al, 1983, Ponka et al, 1984, Rohekar et al, 2008, Rudwaleit et al, 2001, Samuel et al, 1995, Schiellerup et al, 2008, Schoenberg-Norio et al, 2010, Short et al, 1982, Ternhag et al, 2008, Thomson et al, 1992, Thomson et al, 1994, Townes et al, 2008a, Tuompo et al, 2013, Uotila et al, 2014, Urfer et al, 2000, Doorduyn et al, 2008, Arnedo-Pena et al, 2010, Eastmond et al, 1983, Melby et al, 1990) in up to 63% of patients with either infection (Supplementary Table 4). The majority of studies reported ReA triggered by Campylobacter ( n  = 14) or NTS infection ( n  = 18) in < 10% of patients with gastroenteritis.…”
Section: Resultsmentioning
confidence: 99%
“…In 5% of cases, arthritis is chronic or relapsing (57). Symptoms typically begin 3 to 40 days postdiarrhea and most commonly affect the knees (58). GBS is an acute paralytic disease of the peripheral nervous system and is seen in approximately 0.1% of Campylobacter cases.…”
Section: Campylobacter Speciesmentioning
confidence: 99%